Ocrelizumab in Early-Stage Relapsing-Remitting Multiple Sclerosis: The Phase IIIb ENSEMBLE 4-Year, Single-Arm, Open-Label Trial - Hartung, Hans-Peter; Benedict, Ralph H B; Berger, Thomas; Bermel, Robert A; Brochet, Bruno; Carroll, William M; Freedman, Mark S; Holmøy, Trygve; Karabudak, Rana; Nos, Carlos; Patti, Francesco; Perrin Ross, Amy; et al. (Neurology, 2024)
BACKGROUND AND OBJECTIVES: Early treatment of multiple sclerosis (MS) reduces disease activity and the risk of long-term disease progression. Effectiveness of ocrelizumab is established in relapsing MS (RMS); however, data in early RMS are lacking. We evaluated the 4-year effectiveness and safety of ocrelizumab as a first-line therapy in treatment-naive patients with recently diagnosed relapsing-remitting MS (RRMS). METHODS: ENSEMBLE was a prospective, 4-year, international, multicenter, single-arm, open-label, phase IIIb study. Patients were treatment naive, aged 18-55 years, had early-stage RRMS with a disease duration ≤3 years, Expanded Disability Status Scale (EDSS) score ≤3.5, and ≥1 clinically reported relapse(s) or ≥1 signs of brain inflammatory activity on MRI in the prior 12 months. Patients received IV ocrelizumab 600 mg every 24 weeks. Effectiveness endpoints over 192 weeks were proportion of patients with no evidence of disease activity (NEDA-3; defined as absence of relapses, 24-week confirmed disability progression [CDP], and MRI measures, with prespecified MRI rebaselining at week 8), 24-week/48-week CDP and 24-week confirmed disability improvement, annualized relapse rate (ARR), mean change in EDSS score from baseline, and safety. Cognitive status, patient-reported outcomes, and serum neurofilament light chain (NfL) were assessed. Descriptive analysis was performed on the intention-to-treat population. RESULTS: Baseline characteristics (N = 678) were consistent with early-stage RRMS (n = 539 patients, 64.6% female, age 40 years and younger; median age: 31.0 years; duration since: MS symptom onset 0.78 years, RRMS diagnosis 0.24 years; mean baseline EDSS score [SD] 1.71 [0.95]). At week 192, most of the patients had NEDA-3 (n = 394/593, 66.4%), 85.0% had no MRI activity, 90.9% had no relapses, and 81.8% had no 24-week CDP over the study duration. Adjusted ARR at week 192 was low (0.020, 95% CI 0.015-0.027). NfL levels were reduced to and remained within the healthy donor range, by week 48 and week 192, respectively. No new or unexpected safety signals were observed. DISCUSSION: Disease activity based on clinical and MRI measures was absent in most of the patients treated with ocrelizumab over 4 years in the ENSEMBLE study. Safety was consistent with the known profile of ocrelizumab. Although this single-arm study was limited by lack of a parallel group for comparison of outcome measures, the positive benefit-risk profile observed may provide confidence to adopt ocrelizumab as a first-line treatment in newly diagnosed patients with early RMS. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that adult patients with early-stage MS who were treatment naive maintained low disease activity (NEDA-3) over 4 years with ocrelizumab treatment; no new safety signals were detected. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier NCT03085810; first submitted March 16, 2017; first patient enrolled: March 27, 2017; available at clinicaltrials.gov/ct2/show/NCT03085810.
Keywords: dospělí; Magnetic Resonance Imaging; Female; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Disability Evaluation; Adolescent; relabující-remitující roztroušená skleróza; imunologické faktory; lidé; magnetická rezonanční tomografie; Treatment Outcome; prospektivní studie; Immunologic Factors; Male; progrese nemoci; Prospective Studies; Multiple Sclerosis, Relapsing-Remitting; Disease Progression; Young Adult; posuzování pracovní neschopnosti; lidé středního věku; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; mužské pohlaví; Middle Aged; mladiství; Humans